Biofuels for Internal Combustion Engines (International Journal of Food and Nutritional Sciences, 2022)
Any fuel made from biomass that is, plant or algal material or animal waste is referred to as a biofuel. Internal combustion engines, particularly in poorer nations, are a significant source of urban air pollution. The growing use of fossil fuels, mostly by the transportation sector, has resulted in environmental degradation, climate change, and a rise in the number of pollution-related health issues. To bridge the gap between internal combustion engines that operate on gasoline or petro diesel and electric propulsion, which is still being investigated, attempts have been made to use bio-fuels combined with fossil fuels to decrease and control emissions. This study look at various forms of biofuels, fuel additives, and the sustainability of these biofuels, as well as biofuel issues and potential improvements for use in various internal combustion engines. New technologies such as electric cars, hybrid vehicles, and electric propulsion are still in the early phases of development, but switching to electric propulsion will undoubtedly result in a significant reduction in hazardous emissions.